Segmental arterial mediolysis with 5 splenic artery aneurysms. A rare finding of a rare disease: Case report and literature review. (2017) - Termos, Salah; Taqi, Ali; Hayati, Hussein; Alhasan, Ameera J.M.S.; Alali, Mohammad; Adi, Ayman
Highlights: The article represents SAM in SAA which is a rare finding in a rare disease and due to the paucity of sample of cases there is no standardization in the management. SAM should be suspected when multiple aneurysms are found in the same anatomic site. Angiography is important to detect adjacent involvement. CT angiography of brain should be done to rule out distal vascular disease. Endovascular option is the first choice but sometimes it is not feasible, in this case was excluded due to anatomical and configuration reasons. Abstract: Introduction: Splenic artery aneurysms (SAA) are uncommon findings. They are usually single and isolated; however they can be multiple; hence vasculopathy and segmental artery mediolysis may be considered. Presentation of case: In our manuscript we present a case of a 54 year old multiparous lady who was discovered incidentally to have a diseased splenic artery containing five SSAs. The largest aneurysm was close to the takeoff of the vessel and the smallest was distal embedded in the splenic hilum. Endovascular option was technically not feasible. Therefore the patient underwent a complete splenic artery resection with splenectomy and the histopathologic examination was suggestive of segmental arterial mediolysis (SAM). Discussion and conclusion: Multiple SAAs remains a rare finding of a rare disease. Complications can be crucial and high index of suspicion is important. Segmental arterial mediolysis can be considered in patients with several aneurysms on one anatomic site; Angiography is the gold standard diagnostic and therapeutic method. Complete splenic artery resection with splenectomy is the best treatment option for solitary vessel involvement.